Neural regeneration in the human central nervous system—from understanding the underlying mechanisms to developing treatments. Where do we stand today? - Kvistad, Christopher Elnan; Kråkenes, Torbjørn; Gavasso, Sonia; Bø, Lars (Frontiers in Neurology, 2024)
Mature neurons in the human central nervous system (CNS) fail to regenerate after injuries. This is a common denominator across different aetiologies, including multiple sclerosis, spinal cord injury and ischemic stroke. The lack of regeneration leads to permanent functional deficits with a substantial impact on patient quality of life, representing a significant socioeconomic burden worldwide. Great efforts have been made to decipher the responsible mechanisms and we now know that potent intra- and extracellular barriers prevent axonal repair. This knowledge has resulted in numerous clinical trials, aiming to promote neuroregeneration through different approaches. Here, we summarize the current understanding of the causes to the poor regeneration within the human CNS. We also review the results of the treatment attempts that have been translated into clinical trials so far.